Trait Emotional Intelligence in Surgeons - Petrides, K. V.; Perazzo, Matheus F.; Pérez-Díaz, Pablo A.; Jeffrey, Steve; Richardson, Helen C.; Sevdalis, Nick; Ahmad, Noweed (Frontiers in Psychology, 2022)
Trait emotional intelligence (trait EI or trait emotional self-efficacy) concerns people’s perceptions of their emotional abilities. In two studies, the authors conducted a comprehensive investigation of this construct in surgeons. We hypothesized that trait EI profiles would differ both within surgical specialties as well as between surgical specialties and other professions. Study 1 (N = 122) compared the trait EI profiles of four different surgical specialties (General, Orthopedic, Head and Neck, and Miscellaneous surgical specialties). Study 2 (N = 462) combined the surgical data into a single target sample, which it compared against samples of engineers, executives and senior managers, lawyers, junior military managers, nurses, and salespeople. Study 1 found no significant differences among the four different surgical specialties or between trainee surgeons. In Study 2, surgeons scored significantly higher on global trait EI than junior military managers, but lower than executives and senior managers, salespeople, and nurses. There were no significant differences against engineers or lawyers. A MANOVA confirmed a similar pattern of differences in the four trait EI factors (Well-being, Self-control, Sociability, and Emotionality). Global trait EI scores correlated strongly with single-question measures of job satisfaction (r = .47) and job performance (r = .46) in the surgical sample. These findings suggest that interventions to optimize the trait EI profiles of surgeons would be helpful in relation to job satisfaction, job performance, and overall psychological well-being.